Metodologias ativas: a sala de aula invertida aplicada ao ensino de trigonometria - Barros, Rosângela Alves de Aquino (2021)
In the present work, we are going to broach up the use of flipped classroom in trigonometry teaching, considering that in traditional classrooms both students find problems in understanding the content and teachers also have difficulties in sharing this content and finding ways to facilitate the understanding of the subject by the students. Trigonometry is one of the subjects that students face most difficulty during high school and because of that many create barriers to its learning. Therefore, through the use of active teaching methodologies, such as flipped classroom, we can just as the methodology itself says inverts the situation and try to reduce the difficulties that students face in the math subject, especially in trigonometry. The work aims to help the teachers of the subject in order to assist in their practice bringing a proposal for teaching mathematics using flipped classroom active methodology. In addition, the work will also bring a report of a flipped classroom application experience during emergency remote education in 2020 during the coronavirus pandemic and an educational product that emerged from that experience.